Favela da Barreira em cena: a ópera de uma resistência tecida na produção de saberes, conhecimentos e identidades - Lemos, Fábia de Castro (2019)
The present research aimed at understanding the formation of the cultural identity of the group of residents of and visitors to Favela da Barreira, as well as the space itself. We have observed the local knowledge and practices that consolidate the framework of the social group, circulating in the daily life of a favela, which is located in Rocha Miranda neighborhood, in the northern area of the State of Rio de Janeiro. Thus, we sought to understand how these productions have contributed to the construction of the peripheral culture in the favela. We begin with the oral life histories of the dwellers and the visitors of the space, who maintained in the discourse certain identity position, contrasting with the stereotype constructed by the common sense that the favela is a homogeneous group. This study was oriented by the aim to understand the construction of knowledge outlined in the spaces of the favela from the established communication codes, expressed by the appropriations of the space itself and by the oral communication. Between the discernment of external standards and the reformulations made in the favela, there are the mechanisms that explain the strategies of the residents to demarcate the group's identity construction and the negotiations with the space. Through the interviews with residents of and visitors to the favela, as well as the analysis of the manifestations and the appropriations of the space, the objective was to understand how daily life mobilizes the construction of knowledge and organizes the group. This can be understood as the immersion of multicultural identity (ies), which depicts the favela as a space of struggles, negotiations and alliances, revealing the very ethos that permeates the favela, in the weaving of memory, time and space.